A eficácia da conciliação on-line na sociedade da comunicação: um estudo sobre as plataformas digitais no estado de São Paulo - Possato, Karim Regina Nascimento (2020)
Studying online conciliation and its effectiveness as an instrument for reaching agreements in the context of contemporary society, permeated by the need for access to information and, consequently, communication, exploring the efficiency of digital platforms in the State of São Paulo, both private and public , constitutes the central theme of the work. Thus, it seeks to understand the conflict from the perspective of its formation and its adequate treatment in the reality of social interactions, which, currently, are largely located in digital communication environments, considering, in this universe, the characteristics of postmodernity, which portray individualism and consumerism as reflections of the reduction of distances, in which time is one of the main factors that indicate the frequent urgency in resolving disputes. To this end, the study is based on the dialectical method of scientific production, with bibliographic surveys on the subject of self-composition, the communication society and digital media as tools of current interaction, as well as using empirical surveys on the effectiveness of conciliation. online as it researches the court decisions that dealt with the agreements reached. The absence of public power in promoting the implementation of digital platforms as a public policy for conflict resolution is noted, despite concluding that online conciliation is an important instrument of social pacification, effective in the extent that agreements are made, efficient in meeting urges and needs related to urgencies and costs, and effective in the inverse proportion in which there are practically no questions about the legitimacy of the agreements.